Effect of short jute fibers on the hydrolytic degradation behavior of poly (lactic acid). - Jiang, N.; Li, Y.; Yu, T.; Li, D.; Shi, Y.
This paper investigates the effect of short jute fibers on the hydrolysis of poly (lactic acid)(PLA)in deionized water at 50 and 60 °C. The water absorption, thermal and mechanical properties (tensile and flexural), morphological structure, as well as molecular weight of jute/PLA composites and PLA were evaluated before and after aging. The results showed that the jute/PLA composites had higher water absorption but approximately equal mechanical properties compared with PLA. This indicates that it is a feasible way to reinforce PLA by adding short jute fibers. Both PLA and jute/PLA composites undergo hydrolysis after aging. Further analysis revealed that as the vibration and mobility of PLA molecular chains were hindered by addition of jute fibers, jute/PLA composites had a slower decline in mechanical properties than PLA, and thus showed a slower hydrolysis. Moreover, the addition of jute fibers resulted in mechanical interlocking, which in turn increased the load carrying capability of jute/PLA composites.
Keywords: NATURAL FIBER COMPOSITES; HYDROLYTIC DEGRADATION; MECHANICAL PROPERTIES; INTERFACE; THERMAL PROPERTIES; HYDROTHERMAL AGING